Analisis Performa Pada Buck Converter Dengan Optimasi APO-PI - kukuh dermawan; Rifqi Firmansyah (Universitas Negeri Surabaya, 2026)
The development of power electronics technology demands a voltage regulation system that has high performance and good stability. One device that is widely used in voltage regulation is the buck converter, which functions to reduce the voltage from a higher level to a lower level efficiently. However, the nonlinear dynamic characteristics of the buck converter can cause a less than optimal system response if the control method used is not appropriate, even though the system is operating under nominal conditions. This study proposes the application of the Arctic Puffin Optimization–Proportional Integral (APO-PI) method to improve the performance of the voltage regulation in the buck converter. The APO algorithm is used to optimize the parameters of the PI controller to obtain a faster, more stable, and more accurate voltage response. The results of the application of the APO-PI method show an increase in system performance in terms of transient response and voltage stability, characterized by reduced overshoot and shorter settling time. Thus, the APO-PI method is effectively used to improve the performance of the buck converter without requiring changes in system operating conditions.